The Use of Artificial Intelligence (AI) in Internal Supervision to Reduce Fraud in the Public Procurement System in Indonesia - Amiruddin, Amiruddin; Syamsuddin, Syamsuddin; Muntu, Sandra Jeanet; Helda, Wa Ode; Rahadi, Gde Made Dwi Praditya (ProBisnis : Jurnal Manajemen, 2024)
Corruption in the public procurement system is a significant challenge in many developing countries, including Indonesia. Artificial Intelligence (AI) technology offers innovative solutions for strengthening internal oversight and early detection of fraudulent activities. This article presents a systematic review of the literature that discusses the application of AI in internal control, focusing on fraud prevention in public procurement in Indonesia. Using the Systematic Literature Review (SLR) method with PRISMA guidelines, this article compiles, identifies, and synthesises relevant research to evaluate the effectiveness of AI and the challenges in its application. The study results show that although AI has great potential to improve accuracy and efficiency in detecting complex fraud patterns, significant barriers related to implementation costs, limited technology infrastructure, and low readiness of human resources in Indonesia are still significant challenges. Policy recommendations include accelerating AI adoption by developing supportive regulations and improving technological competence in the public sector.